Reliability of the Southampton examination schedule for the diagnosis of upper limb disorders in the general population. Issue 12 (1st December 2002) - Walker-Bone, K; Byng, P; Linaker, C; Reading, I; Coggon, D; Palmer, K T; Cooper, C
Abstract : Background: Epidemiological research in the field of soft tissue neck and upper limb disorders has been hampered by the lack of an agreed system of diagnostic classification. In 1997, a United Kingdom workshop agreed consensus definitions for nine of these conditions. From these criteria, an examination schedule was developed and validated in a hospital setting. Objective: To investigate the reliability of this schedule in the general population. Methods: Ninety seven adults of working age reporting recent neck or upper limb symptoms were invited to attend for clinical examination consisting of inspection and palpation of the upper limbs, measurement of active and passive ranges of motion, and clinical provocation tests. A doctor and a trained research nurse examined each patient separately, in random order and blinded to each other's findings. Results: Between observer repeatability of the schedule was generally good, with a median κ coefficient of 0.66 (range 0.21 to 0.93) for each of the specific diagnoses considered. Conclusion: As expected, the repeatability of tests is poorer in the general population than in the hospital clinic, but the Southampton examination schedule is sufficiently reproducible for epidemiological research in the general population.